Odpowiedzi

Najlepsza Odpowiedź!
2009-11-05T22:39:49+01:00
X²+x-(2x³-5x)=3x+4-(x²+x)
x²+x-2x³+5x=3x+4-x²-x
-2x³+2x²+4x-4=0
-2x²(x-1)+4(x-1)=0
(x-1)(-2x²+4)=0
x-1=0 v -2x²+4=0
x=1 v -2x²=-4
x=1 v x=√2 v x=-√2
tylko x=1 jest liczbą całkowita
b)a₁=2-5=-3
a₂=1+1=2
r=a₂/a₁
r=2+3=5
an=a₁+(n-1)r
an=-3+(n-1)5=-3+5n-5=5n-8
2009-11-05T22:50:57+01:00
2x³ - 5x - x² -x = x² + x - 3x -4
2x³ - x² -6x = x² -2x -4
2x³ - 2x² - 4x + 4= 0
(2x³ -4x) - (2x² -4) = 0
2x(x² -2) - 2(x² -2) = 0
(2x- 2)(x² - 2) = 0

x=1 lub x=√2 lub x= - √2

Liczby muszą być całkowite co wychodzi tylko dla x= 1.


a₁ = -3
a₂ = 2
a₃ = 7

r = 5

an = a₁ + (n-1)r

an= -3 + (n-1)*5 = 5n - 5 -3 = 5n - 8